2006
DOI: 10.1007/s10533-005-0711-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-site Comparison of Variability of DOC and Nitrate c–q Hysteresis during the Autumn–winter Period in Three Mediterranean Headwater Streams: A Synthetic Approach

Abstract: The forms, rotational patterns and trends of hysteretic loops of dissolved organic carbon (DOC) and nitrate (NO 3 ) were investigated in three headwater Mediterranean streams during one autumn-winter period using two biogeochemical descriptors summarizing the changes in solute concentrations (DC) and the overall dynamics of each hysteretic loop (DR). The study had two aims: (1) to examine whether the variability of solute hysteretic loops monitored in different streams during cold seasons followed a consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 43 publications
(48 reference statements)
11
59
1
1
Order By: Relevance
“…Hornberger et al, 1994;Butturini et al, 2006;Jeong et al, 2012). This was also reported in studies where DOC was found to originate mainly from riparian wetland soils (McGlynn and McDonnell, 2003;Hood et al, 2006).…”
Section: Temporal Dynamics Of Doc In Runoffsupporting
confidence: 75%
See 1 more Smart Citation
“…Hornberger et al, 1994;Butturini et al, 2006;Jeong et al, 2012). This was also reported in studies where DOC was found to originate mainly from riparian wetland soils (McGlynn and McDonnell, 2003;Hood et al, 2006).…”
Section: Temporal Dynamics Of Doc In Runoffsupporting
confidence: 75%
“…Hysteretic relationships between discharge and solute concentrations have observed, among others, by Hornberger et al (1994), Evans and Davies (1998), Butturini et al (2006), Raymond and Saiers (2010), Pellerin et al (2012) and Jeong et al (2012). Evans and Davies (1998) proposed the hysteretic concentration/discharge relationship for the analysis of episode hydrochemistry.…”
Section: Introductionmentioning
confidence: 98%
“…3). The lower DOC concentrations during the falling hydrograph indicate that the DOC storm response is hysteretic (Butturini et al 2006) and may, for example, reflect temporary depletion of the terrestrial DOC supply due to soilwater flushing (Hornberger et al 1994;Boyer et al 2000) or, perhaps, changes in the timing of runoff contributions from the riparian zone and hill slope during the course of a rainfall event (Hinton et al 1998;McGlynn and McDonnell 2003). DOC that appears in small streams during hydrologic events is derived primarily from allochthonous terrestrial sources (Royer and David 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hysteresis refers to differing relationships between DOC concentration and discharge on the rising and falling limbs of the hydrograph during a runoff event (Evans and Davies 1998). The size, direction, and slope of hysteresis loops can reflect the source and the relative magnitudes and timing of allochthonous inputs of DOM (Butturini et al 2006). Clockwise directions of change over the course of a hydrologic event suggest that DOM sources are well connected to each other and proximal to the stream, while counterclockwise directions suggest DOM sources are disconnected from each other and distal from the stream.…”
Section: Hypothesis: the Interactive Effects Of Riverine Biogeochemicmentioning
confidence: 99%